1972
DOI: 10.1136/adc.47.252.261
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin Levels in Normal Infants Aged 3 to 24 Months, and the Effect of Iron

Abstract: From Bristol Royal Hospitalfor Sick Children, Bristol Burman, D. (1972). Archives of Disease in Childhood, 47, 261. Haemoglobin levels in normal infants aged 3 to 24 months, and the effect of iron. From the age of 3 to 24 months, capillary Hb levels were measured on normal term infants who received no medicinal iron from any source. The mean and standard deviations are recorded at 3-monthly intervals. Females had a higher Hb than males when considered as an overall trend throughout the period. There was no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

1974
1974
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…In this study females had higher Hb levels than males, a similar sex difference being reported by Burman (1972), and males gained slightly more weight than females during the year, the negative correlation we found between weight gain and Hb level partly explaining this sex difference. No correlation between weight gain and Hb level was found by Burman or by Beal, Meyers, and peak at 8 months of age, with 76% of children below 11 g/100 ml and 41% below 10 g/100 ml.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study females had higher Hb levels than males, a similar sex difference being reported by Burman (1972), and males gained slightly more weight than females during the year, the negative correlation we found between weight gain and Hb level partly explaining this sex difference. No correlation between weight gain and Hb level was found by Burman or by Beal, Meyers, and peak at 8 months of age, with 76% of children below 11 g/100 ml and 41% below 10 g/100 ml.…”
Section: Discussionsupporting
confidence: 86%
“…In this study the 4 girls who had the disease were comparable to the other children in both growth and health, their heights and weights being close to the median at 12 months of age, and the incidence of infection among them being no different from the rest of the group. Gray (1971) normal weights and heights in Jamaican children with sickle cell disease, but Booker, Scott, and Ferguson (1964) reported depressed weights after 4 months of age in Washington, D.C. Hb levels in this study were compared with those found by Burman (1972) in a study in Bristol, U.K., in which low birthweight babies and twins were also excluded from analyses. The mean Hb levels of the Kingston children were lower than those of the Bristol children at all ages (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…We have found only a few papers in which Hb levels in infancy differed between girls and boys. In the United Kingdom, Burman 23 found that girls had a significantly higher Hb concentration, but, as in our study, the differences were small. The largest difference in mean Hb in infancy was found at 6 months when boys had a mean Hb level of 116.9 g/l, whereas girls had a mean level of 119.4 g/l.…”
Section: Discussioncontrasting
confidence: 68%
“…Many of the published data on normal haemoglobin and the definition of anaemia are derived from studies in the developing world4 with few contemporary population based data from the UK. [5][6][7][8] In order to identify the optimum age to screen for iron deficiency we are investigating the normal distribution of haemoglobin and ferritin and assessing the relationship of these to the developmental progress of the child, in a representative population sample from the Avon Longitudinal Study of Pregnancy and Childhood (ALSPAC). This is a geographically based cohort study investigating factors influencing health and development of children, and provides an ideal medium for determining the current distributions of haemoglobin and ferritin concentrations in young children.…”
mentioning
confidence: 99%